Drug Treatment of Obsessive Compulsive Disorder - Nazar, Zahid; Farooq, Saeed; Mufti, Khalid A. (Journal of Postgraduate Medical Institute, 2011)
Obsessive compulsive disorder is a common, usually chronic and sometimes disabling neuro psychiatric syndrome of unknown aetiology. In obsessive compulsive disorder, the irrational ideas or the impulse persistently intrudes into theawareness, obsessions (constantly recurring thoughts such as fear of exposure to germs) and compulsions repetitive action such as washing hand many times) are recognized by the idividual as absurd and are resisted but axiety is alleviated only by ritualistic performance of the action or by deliverate contemplation of the intruding idea or emotion. Many patients do not mention the symptoms and must be asked about them. Male - female ratio is similar, highest rate of the obsessive compulsive disorder occuring in young, divorced, separtated and unemployed (all high stress categories).